Natural convection heat transfer analysis of copper-alumina/water hybrid nanofluid in a U-shaped enclosure / Muhammad Solleh Asmadi - Muhammad Solleh , Asmadi (2022)
Heat transfer by natural convection inside a U-shaped enclosure is investigated while considering the working fluid as hybrid nanofluid. Copper (Cu) and alumina (Al2O3) nanoparticles are suspended in pure water to form hybrid nanofluids. Various aspects of physical properties are varied to see the effect of each factor on the overall heat transfer rate. The nanoparticle shape, the enclosure inclination angle, the enclosure obliqueness angle, the length and position of the heating element, the thermal profiles at the hot wall, the waviness of the walls, and the cold baffle are thoroughly varied to find the most suitable combinations of parameters for certain applications. The governing equations are transformed to their dimensionless form using a set of dimensionless variables to ensure generality. The Galerkin weighted residual finite element method is employed to solve the problem with the entire domain being discretized to a finite number of threenode triangular elements. A damped Newton-Raphson iteration algorithm is used as a convergence condition. Several grid dependency tests are done to ensure the results obtained through the numerical procedure are not affected regardless of the grid configurations. Numerical comparisons with the previously published numerical and experimental data are conducted to ascertain the validity and reliability of the numerical algorithm and formulations. The heat transfer rate within the enclosure is measured by using the local and average Nusselt numbers. A comparison of the heat transfer rate between Cu/water and Al2O3/water with Cu-Al2O3/water hybrid nanofluid is done to examine the advantages of using hybrid nanofluid compared to mono nanofluids. The nanoparticle volume fraction and its ratios, the Rayleigh number, the cold rib dimension, the cold rib position, the hot thermal profiles, the heater element length and position, the enclosure inclination angle, the enclosure obliqueness angle, the adiabatic and hot waviness, and the cold baffle length are varied and investigated extensively by examining the streamlines, the isotherms, the vorticity, the average Nusselt number, the local Nusselt number across the hot wall and cold rib, the velocity profile, the absolute maximum stream function value and the maximum vorticity for several combinations of parameters. It is observed that the heat transfer rate increases as the Rayleigh number increases and the benefit of using hybrid nanofluid in terms of thermal performance exceeds those of pure water and mono nanofluids in the thermal dissipation rate. A symmetric enclosure configuration will be preferable for applications where a high heat transfer rate is needed.